U.S. national security and the intelligence services - Benny, Daniel J. (Boca Raton, FL : CRC Press, 2023)
"While there are books that cover national security, intelligence collection, intelligence analysis, and various intelligence services, U.S. National Security and the Intelligence Services is the first, all-inclusive book to examine intelligence agencies as a direct function of national security. It serves as a comprehensive text for students and a resource for those in the intelligence profession and national security scholars. U.S. National Security and the Intelligence Services provides a handy reference outlining the framework, and the processes, that comprise the US intelligence apparatus"--
National Security and the Need for Intelligence -- United States Intelligence Services -- United States Key Allied Intelligence Services -- Key Hostile Nations Intelligence Services -- Categories of Intelligence -- Intelligence Collection, Processing, Analysis and Dissemination Methods -- Determining the Value of Intelligence -- Intelligence Analysis -- Selected Intelligence Resources.
OCLC-licensed vendor bibliographic record.
Keywords: Intelligence service -- United States; National security -- United States; POLITICAL SCIENCE / Political Freedom & Security / Intelligence; POLITICAL SCIENCE / Political Freedom & Security / Terrorism; POLITICAL SCIENCE / Political Freedom & Security / Law Enforcement